Geography, professional practice and continuing teacher training in the current context (Praxis Educativa, 2024)
This article shares the teacher training experience developed during the year 2023. The proposal consists of an Athenaeum for teachers of Geography and Social Sciences in secondary and tertiary education. From recovering the current educational context focused on the needs and requirements that the secondary level demands, theoretical - practical classes are developed in which we discuss concerns, critical knots, pending challenges, which require thinking with others to build collaboratively powerful teaching and learning. In this sense, as specific training educators, we designed the device with the purpose of inviting reflection on teaching practices, to position ourselves through action in the search for possible alternatives in the face of educational emergencies. Encouraging us to ask ourselves questions, hypothesize results from a creative perspective, recognizing everyday situations of “doing and being at school” are part of the transformations that we imagine to improve and empower ourselves in our profesional work.
Keywords: Geography, professional practice, secondary and tertiary education